CORRELATION OF PARENTS' KNOWLEDGE AND SOCIOECONOMIC STATUS WITH THE EXPERIENCE OF TOOTH EXTRACTION - Winda Aulia Putri; Ika Kusuma Wardani; Isnur Hatta (FKG Unlam, 2022)
Background: Tooth extraction that is not replaced with dentures causes decreased masticatory and speech functions, from irregular tooth arrangement to disorders of temporomandibular joint. Public awareness in filling their teeth is still lacking due to their preference to remove problematic teeth than treating them. Socioeconomic status in the form of work, income, and education affects the ability of a family to meet the need for health services. The low level of public knowledge about tooth extraction causes the perception that if a tooth is aching, then tooth extraction is the most appropriate treatment. Purpose: The purpose of this research was to analyze the relationship between knowledge and socioeconomic status of parents with the experience of tooth extraction in students at SMPN 6 Banjarmasin. Methods: This research was an observational analytic research with a cross sectional approach. The research sample was 34 students of SMPN 6 Banjarmasin obtained using the correlation formula. Collecting data was performed using a questionnaire that has been tested for validity and reliability. Data analysis was performed using Spearman's test. Results: The results of the Spearman test showed a significant relationship between knowledge and socioeconomic status of parents and experience of tooth extraction (p<0.05). Conclusion: There is a significant correlation between knowledge and socioeconomic status of parents with the experience of tooth extraction at SMPN 6 Banjarmasin. Keywords: Adolescent, Knowledge, Parents, Socioeconomic Status, Tooth Extraction